Analysis of Eccentricity-Based Topological Invariants with Zero-Divisor Graphs - Zhi-hao Hui; Abdul Rauf; Muhammad Mohsin Abbas; Adnan Aslam (Journal of Function Spaces)
Let R=Z♭1♭2♭3×Zq2 be a commutative ring, where ♭1,♭2,♭3 are distinct primes, and q is any prime integer. A zero divisor graph JR of ring R is a graph with vertex set consist of zero divisors elements of R and any two vertices a,b are adjacent if and only if ab=0. A topological index is a numerical number associated with the graph and may be helpful to correlate the graph with certain of its physical/chemical properties. In this paper, we have computed some eccentricity based topological indices of JR, namely, atom-bond connectivity index (ABC5), eccentricity-based harmonic index of fourth type (H4J), geometric-arithmetic eccentricity index (GA4J), eccentricity-based third Zagreb index, and eccentricity-based first Zagreb index.